Photochemical smog: Mechanism, ill-effects, and control - Kumar P.; Mohan D. (My University, 2025)
The homocentric model of development considers this highly intelligent species not as a part of nature, but as an independent, isolated entity capable of conquering nature. Excessive stress, only on material development without due care to environmental health, has led to unimaginable deterioration of quality of air, water, arid soil - the fundamental constituents of biosphere. The industrial revolution has been the central cause of increase in pollutants in the atmosphere. Photochemical smog is one of the most dangerous effects of pollution on atmosphere. It is a condition that develops when oxides of nitrogen and VOCs (volatile organic compounds) interact in the presence of sunlight to produce a mixture of hundreds of hazardous chemicals, which have a major toxic effect on environment and bio-organisms. The oxides of nitrogen are formed in favourable conditions in high temperature of 3000-4000 °F. There is an urgent need to understand the mechanism of formation of photochemical smog and to practise science and technology in an ethical way with respect to the protection of environment.